Newsroom integration in Catalan local newspapers - Masip Masip, Pere; Micó Sanz, Josep Lluís; Ruiz Caballero, Carles; Domingo Santamaría, David; Nogué Regàs, Anna (Estudios sobre el Mensaje Periodístico, 2011)
The aim of this article is examine the characteristics of newsrooms’ organization of Catalan local media as a part of media convergence. Data was obtained from a survey distributed among media members of the Catalan Association of Local Newspapers, with a response rate of 45%, and 19 in-depth interviews with journalists and managers of 8 media groups. Companies were selected taking into account a wide range of variables: geographical distribution, periodicity, circulation, etc. Results show media convergence does not mean newsroom integration, but media groups usually develop some kind of integrated production. Formulas developed by media are diverse, with different levels of integration.
Keywords: Media convergente; newsroom integration; local media; Catalonia.